(D^2+2D+5)y=xe^x
Given: "(D^2+2D+5)y=xe^x"
Here, "D=\\frac{d}{dx}"
So, we can rewrite it as: "\\frac{d^2y}{dx^2}+2\\frac{dy}{dx}+5y=xe^x" ... (i)
First, we find "y_c" , complimentary function.
Consider "\\frac{d^2y}{dx^2}+2\\frac{dy}{dx}+5y=0"
Its auxiliary equation is: "m^2+2m+5=0"
On solving by quadratic formula,
"m=\\frac{-2\\pm\\sqrt{2^2-4(1)(5)}}{2(1)}=\\frac{-2\\pm\\sqrt{4-20}}{2}=-1\\pm2i"
Thus, the solution of homogeneous equation is:
"y_c=e^{-1x}(A\\cos2x+B\\sin2x)=Ae^{-x}\\cos2x+Be^{-x}\\sin2x"
Now, we find particular solution of non-homogeneous equation.
Assume "y=(ax+b)e^x" be the solution ...(ii)
We find a and b by substitution and comparison.
On differentiating (ii) w.r.t "x" ,
"\\frac{dy}{dx}=(ax+b)e^x+(a)e^x\n\\\\ \\Rightarrow\\frac{dy}{dx}=(ax+a+b)e^x"
Again, differentiating it w.r.t "x" ,
"\\frac{d^2y}{dx^2}=(ax+a+b)e^x+ae^x\n\\\\ \\Rightarrow \\frac{d^2y}{dx^2}=(ax+2a+b)e^x"
Now substituting these values in (i), we get,
"(ax+2a+b)e^x+2(ax+a+b)e^x+5(ax+b)e^x=xe^x\n\\\\ \\Rightarrow (ax+2a+b)+2(ax+a+b)+5(ax+b)=x"
"\\Rightarrow (8a)x+(4a+8b)=1x+0"
On comparing,
"8a=1\\Rightarrow a=\\frac 1 8\n\\\\ 4a+8b=0 \\Rightarrow 8b=-4a \\Rightarrow b=-\\frac{a}{2}"
So, "b=-\\frac1 2 \\times \\frac 1 8=-\\frac 1 {16}"
So, "y_p=(\\frac1 8x-\\frac 1 {16})e^x=\\frac{xe^x}{8}-\\frac{e^x}{16}"
Thus, "y(x)=y_c+y_p"
"=Ae^{-x}\\cos2x+Be^{-x}\\sin2x+\\frac{xe^x}{8}-\\frac{e^x}{16}"
Answer: "y(x)=Ae^{-x}\\cos2x+Be^{-x}\\sin2x+\\frac{xe^x}{8}-\\frac{e^x}{16}"
Comments
Leave a comment